2018
DOI: 10.1080/16070658.2018.1515394
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake as a cardiovascular risk factor: a cross-sectional study of bank employees in Accra

Abstract: Objectives: To determine the dietary and nutrient intakes of bank employees in Accra in relation to recommended dietary intake for the control of cardiovascular diseases (CVD). Design: The study was a cross-sectional study. Methodology: A structured validated questionnaire was used to obtain demographics. A 3-day 24-hour dietary recall and usual food intake questionnaire were used to obtain information on food intakes and dietary pattern of the respondents. Food models, household measures and photos of common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
1
1
Order By: Relevance
“…Low magnesium intakes have been reported in similar populations in Ghana and other countries. Frimpong, et al [ 17 ] assessed the dietary intakes of bank employees in Ghana using ESHA and reported a mean dietary magnesium intake of 88 mg/day for women, which was lower than our results. The difference could be attributed to differences in the dietary patterns of the urban population in Frimpong’s study versus the peri-urban dietary patterns of our study participants, as well as the employment status of the participants, which in Frimpong’s study included bank employees, whereas our study participants, while mostly employed, were mostly involved in unskilled or skilled labor such as hairdresser and trader.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Low magnesium intakes have been reported in similar populations in Ghana and other countries. Frimpong, et al [ 17 ] assessed the dietary intakes of bank employees in Ghana using ESHA and reported a mean dietary magnesium intake of 88 mg/day for women, which was lower than our results. The difference could be attributed to differences in the dietary patterns of the urban population in Frimpong’s study versus the peri-urban dietary patterns of our study participants, as well as the employment status of the participants, which in Frimpong’s study included bank employees, whereas our study participants, while mostly employed, were mostly involved in unskilled or skilled labor such as hairdresser and trader.…”
Section: Discussioncontrasting
confidence: 95%
“…Both the ESHA Food Processor and NDSR programs have been used to estimate nutrient intakes in several populations [ 17 , 22 27 ]. We selected ESHA Food Processor as the principal software in our study since it is regularly used in West Africa to assess magnesium intake [ 9 ], but we also wanted to compare the results to other systems, such as NDSR, which is widely used in the United States and there is currently no formal guidance as to which should be used in Ghana [ 10 ].…”
Section: Discussionmentioning
confidence: 99%